Diversity, population structure, and regeneration potential of tree species in five sacred forests of western Odisha, India. Issue 1 (2nd January 2019) - Pradhan, Antaryami; Ormsby, Alison; Behera, Niranjan
ABSTRACT: From September 2015 to February 2016, we collected field data to study the tree species diversity, population structure and regeneration potential of five sacred forests of western Odisha, India, that differ in size, associated deities, and local communities. The close association of sacred forests with local people represents a community-based, participatory approach to conservation. Our quantitative analysis in five sites documented 78 tree species of 66 genera and 33 families. Tree density and species diversity were higher than previously reported for the forests of the Eastern Ghats, India. Population structure and regeneration potential in four out of five study sites showed a higher percentage of density in the seedling and sapling layers, demonstrating that these sites are regenerating. However, in the Gugarpat sacred forest, the population structure revealed large numbers of mature trees with a stable population structure. In our study, large proportions of species had either poor regeneration potential or were not regenerating. Hence, management strategies are needed to conserve these species. Our study documents the diversity, population patterns, and regeneration of the tree species of five sacred forests, which may help in further management and conservation of the biodiversity of sacred forests in India and globally.